Penambahan Tepung Kulit Pisang Terfermentasi Dalam Ransum Terhadap Komposisi Karkas Ayam Kampung - I Nyoman Putra Anugrah Agastya; Yan Tonga; Ni Ketut Mardewi (Fakultas Pertanian, Universitas Warmadewa, 2022)
This study aims to determine the effect of adding fermented banana peel flour in the ration to the physical composition of native chicken carcasses. Design used in this study was a Completely Randomized Design (CRD) consisting of 5 treatments and 3 replications, while. The treatments were R0 (Native Chicken that was not given fermented banana peel flour), R1 (Native chicken fed a ration containing 2.5% of fermented banana peel flour), R2 ( Native Chicken fed a ration containing 5% fermented banana peel flour) R3 (Native chickens were given a ration containing 7.5% fermented banana peel flour) and R4 (Native chickens were given a 10% fermented banana peel flour). Ration fermented banana peel flour had a significant effect (P<0.05) on meat weight, skin and subcutaneous fat on the thigh chart, while the effect was not significant (P>0.05) on the weight of meat, bone, skin and subcutaneous fat of the chest and thigh bones